Quantifying burden of intravitreal injections: questionnaire assessment of life impact of treatment by intravitreal injections (QUALITII). Issue 1 (19th December 2022) - Wang, Rui; McClard, Cynthia K; Laswell, Stephen; Mahmoudzadeh, Raziyeh; Salabati, Mirataollah; Ammar, Michael; Vannavong, Jordyn; Aziz, Aamir A; Ewald, Amy; Calvanese, Allison V; Lehman, Erik B; Fried, Sagit; et al.
Abstract : Aim: To quantify the areas of burden experienced by patients requiring repeated intravitreal injections (IVI) in the management of exudative retinal diseases. Methods: The validated Questionnaire to Assess Life Impact of Treatment by Intravitreal Injections survey was administered to patients at four retina clinical practices across four US states. The primary outcome measure was Treatment Burden Score (TBS), a single score assessing overall burden. Results: Of 1416 (n=657 age-related macular degeneration; n=360 diabetic macular oedema/diabetic retinopathy; n=221 retinal vein occlusion; n=178 other/uncertain) patients, 55% were women with an average age of 70 years. Patients most frequently reported receiving IVI every 4–5 weeks (40%). The mean TBS was 16.1±9.2 (range 1–48; scale of 1–54), and the TBS was higher in patients with diabetic macular oedema and/or diabetic retinopathy (DMO/DR) (17.1) compared with those with age-related macular degeneration (15.5) or retinal venous occlusive (15.3) (p=0.028). Though the mean level of discomfort was quite low (1.86) (scale 0–6), 50% of patients reported experiencing side effects more than half of the visits. Patients having received fewer than 5 IVI reported higher mean anxiety levels before (p=0.026), during (p=0.050) and after (p=0.016) treatment compared with patients having received more than 50 IVI. After the procedure, 42% of patients reported restrictions from usual activities due to discomfort. Patients reported a high mean satisfaction rating of 5.46 (scale 0–6) with the care of their diseases. Conclusions: The mean TBS was moderate and highest among patients with DMO/DR. Patients with more total injections reported lower levels of discomfort and anxiety but higher disruption to daily life. Despite the challenges related to IVI, the overall satisfaction with treatment remained high.